Estimation of Shallow Groundwater Recharge Using a Gis-Based Distributed Water Balance Model - Graf, Renata; Przybyłek, Jan (Quaestiones Geographicae, 2014)
In the paper we present the results of shallow groundwater recharge estimation using the WetSpass GISbased distributed water balance model. By taking into account WetSpass, which stands for Water an Energy Transfer between Soil, Plants and Atmosphere under quasi-Steady State, for average conditions during the period 1961-2000, we assessed the spatial conditions of the groundwater infiltration recharge process of shallow circulation systems in the Poznan Plateau area (the Great Poland Lowland in western Poland), which is classified as a region with observed water deficits. For three temporal variants, i.e. year, winter and summer half-years, we determined using the geological infiltration method by about 5-10% on average, marginally by 20%.